Banality of Transgender Performance in the Public Sphere: The Views of Religious Leaders and the Goverment from the Maqāṣid Al-Syarī’ah Perspective (a Case Study in Bone City) - Laura, Riska Islamia; Hasan, Hamzah; Kurniati, Kurniati (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2023)
This study discusses the maqāṣid al-syarī’ah perspective on the views of religious leaders and the government regarding the performance of transgender women in the public space of the Bone district which is already at the banal stage (considered normal, normalized). This type of research uses descriptive qualitative field research with two approaches, namely normative theology (syar’ī) and phenomenology. The main data source was obtained from interviews with religious leaders and the government of Bone district. Observation, interview, and document study techniques are the data collection techniques used. The research results obtained from the interview session found that there were two main factors causing the banality of transgender performance in the public spaces of Bone district. First, the human rights factor. Second, the existence of the Bissu culture (transgender) as part of the Bugis history of Bone which has long been accepted by society. Based on the analysis of maqāṣid al-syarī’ah, these two factors are contrary to sharia (Islamic law). The position of human rights is not higher than the position of Shari’a, this is based on the order of al-ḍarūriyāt al-khams where the order of hifz al-nafs (care of the soul) is in second place under hifz al-din (maintenance of religion). Furthermore, the reason that the acceptance of transgender women that has been taking place for a long time, like acceptance of Bissu, cannot be accepted based on maqāṣid al-syarī’ah. Because it is clear in the Shari’a that harm cannot be allowed to go unpunished even though it is considered to have happened for a long time by most people. As the law of fiqh rules الضَّرَرُلاَيَكُونُ قَدِ يمً. Keywords: Banality, Transgender, Maqāṣid Al-Syarī’ah